2018
DOI: 10.1002/mc.22842
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes related to inflammation and obesity and colorectal adenoma risk

Abstract: We previously investigated the association between single nucleotide polymorphisms (SNPs) in genes related to obesity and inflammation and colorectal cancer in the CLUE II cohort. However, the relationships between these SNPs and colorectal adenomas have not been well evaluated. In a nested case-control study of 135 incident adenoma cases and 269 matched controls in the CLUE II cohort (1989-2000), we genotyped 17 candidate SNPs in 12 genes (PPARG, TCF7L2, ADIPOQ, LEP, IL10, CRP, TLR4, IL6, IL1B, IL8, TNF, RNAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Some GWA studies have also reported that some polymorphisms of the IL-6 gene are insignificantly associated with blood cancer [ 13 25 ] and significantly associated with breast cancer [ 26 36 ] whereas some other studies [ 37 – 40 ] reported no association with breast cancer. Similarly, for cervical and colon cancer development, some studies reported a significant association [ 41 46 and 49 56 respectively] whereas other studies reported no significant association [ 44 , 47 , 48 , 57 61 respectively]. The same scenario persists for liver cancer: associated [ 62 68 ] and not “associated [ 69 71 ]; lung cancer: associated [ 72 77 ] and not associated [ 78 83 ]; prostate cancer: associated [ 11 , 84 91 ] and not associated [ 92 98 ]; stomach cancer: claimed a significant association [ 106 112 ] and some other studies claimed insignificant association [ 111 , 113 115 ].…”
Section: Introductionmentioning
confidence: 95%
“…Some GWA studies have also reported that some polymorphisms of the IL-6 gene are insignificantly associated with blood cancer [ 13 25 ] and significantly associated with breast cancer [ 26 36 ] whereas some other studies [ 37 – 40 ] reported no association with breast cancer. Similarly, for cervical and colon cancer development, some studies reported a significant association [ 41 46 and 49 56 respectively] whereas other studies reported no significant association [ 44 , 47 , 48 , 57 61 respectively]. The same scenario persists for liver cancer: associated [ 62 68 ] and not “associated [ 69 71 ]; lung cancer: associated [ 72 77 ] and not associated [ 78 83 ]; prostate cancer: associated [ 11 , 84 91 ] and not associated [ 92 98 ]; stomach cancer: claimed a significant association [ 106 112 ] and some other studies claimed insignificant association [ 111 , 113 115 ].…”
Section: Introductionmentioning
confidence: 95%
“…In that article, only five case–control studies were summarized. Since then, several new case‐control studies were published (Huang et al, 2018; Markt et al, 2014; Nimptsch et al, 2015; Zhang et al, 2015; Zhou & Bai, 2019). We pooled them together and observed that the CRP rs2808630 T>C polymorphism are also associated with risk of cancer in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the relatively small sample size, it is most likely to lead to significant differences in the results. The purpose of the present analysis was to comprehensively investigate the correlation between the two CRP variants and susceptibility of cancer (Chaturvedi et al, 2010; Chen, Liu, Zhao, & Zang, 2019; Gong et al, 2013; Huang et al, 2018; Markt et al, 2014; Minamiya et al, 2010; Motoyama et al, 2009; Nimptsch et al, 2015; Ognjanovic et al, 2010; Pierce et al, 2009; Poole et al, 2009; Siemes et al, 2006; Slattery et al, 2011; Tsilidis et al, 2009; Xu et al, 2013; Yang, Huang, Chang, & Lin, 2011; Zhang et al, 2015; Zhou & Bai, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One of the master regulators of CRC-associated inflammation is Interleukin 1 β (IL1β). IL1β participates in the activation of Nuclear Factor Kappa-light-chain-enhancer of activated B cells (NF-κB)-driver molecular machinery [61] and, for this reason, was classified as pivotal signal molecule contributing to CRC pathogenesis in both preclinical studies, exploiting either the AOM/DSS [62] or the genetic models of CRC [52] and human samples [63], where polymorphisms in its gene and receptors are associated with this disease [64].…”
Section: Pro-inflammatory Signals In Crcmentioning
confidence: 99%
“…In the following sections, we will highlight studies pointing out resolving ω-3and ω-6-derived lipid mediators as possible molecules for cancer treatment. [64] Preclinical study on APC ∆716 mouse model COX-2 derived AA lipids are essential for tumor growth Calviello et al, 2004 [65] In vitro study on colon cancer cells EPA and DHA block COX-2 expression Fluckiger et al, 2016; Siddiqui et al, 2008 [67,68] In vitro study on colon cancer cells DHA blocks AA-induced proliferation and apoptosis Sarabi et al, 2019 [69] Preclinical study on APC min/+ mouse model and in vitro study on colon cancer cells ω-3 PUFAs enhance apoptosis via specific promoter methylation Liu et al, 2016 [70] Preclinical study on APC…”
Section: The Resolution Of Crc-associated Inflammation Through the ω-mentioning
confidence: 99%